MEASURING THE IMPACT OF INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) TO FINANCIAL INFORMATION OF PORTUGUESE COMPANIES - Silva, Francisco José Ferreira; Couto, Gualter Manuel Medeiros do; Cordeiro, Ruben Mota (Revista Universo Contábil, 2008)
To increase efficiency of the European finance market, the European Union (EU) recently forced all public companies to publish their financial disclosures with the support of the International Financial Reporting Standards (IFRS), emanated by the International Accounting Standards Board (IASB), beginning January 1, 2005. In this paper, we measure the impact of the application of IFRS to financial information of Portuguese public companies belonging to the Eurolist by Euronext Lisbon. The results show that the Balance Sheet and Income Statement structures of the firms studied suffered relevant accounting conversions in the process of compliance. Nevertheless, we did not find a clear pattern for the accounting variations. IFRS implementation conditioned the measure made to the performance and the financial position of the business companies in Portugal.